Improving Knowledge of Senior High School Adolescents About Reproductive Health Through Health Education - Mella Yuria R.A.; Royani (PT Syamilah Literasi Islami, 2024)
Reproductive health problems in adolescents are closely related to risky adolescent behavior, one of which is because there are still many adolescents who do not understand reproductive health. This research aims to determine the extent of the increase in knowledge and attitudes of high school adolescents about reproductive health through counseling. This research design uses One Group Pretest and Postest. The population of this study were all students at SMK Al Falah Mampang Prapatan South Jakarta. The research sample was all X II class students at SMK Al Falah, totaling 100 students. Data analysis uses a test of two dependent means or dependent T test (paired T test). This research instrument uses a questionnaire. The results showed an increase in the mean score of knowledge of high school adolescents after being given education through counseling on Reproductive Health of 0.136 to 0.160. p value = 0.000 <0.005 which means there is an effect of counseling on reproductive health on adolescent knowledge at SMK Al-Falah Jakarta. Reproductive health counselling efforts on adolescents have an effect in increasing adolescents' knowledge of reproductive health. It is expected that if adolescents know about reproductive health, they will know the impact that will be caused if they do not maintain their reproductive health.